2023
DOI: 10.1002/adfm.202215215
|View full text |Cite
|
Sign up to set email alerts
|

Marangoni Flow Driven via Hole Structure of Soluble Acene–Polymer Blends for Selective Nitrogen Dioxide Sensing

Abstract: The correlations between semiconductor type and gas sensing properties in soluble acene/polymer blends have not yet been examined. Here, the phase separation mechanism in pseudo‐liquid phase blend film is investigated and an unusual solid‐state morphology that is effective for amperometric gas sensing performance is demonstrated. In 6,13‐bis(triisopropylsilylethynyl) pentacene (TIPS–pentacene)/poly(fluorine‐co‐triarylamine) (PTAA) blend, two phases are uniformly mixed, without being completely phase‐separated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In this work, we report an optically switchable organic synapse based on a simple OFET structure with 6,13-bis(triisopropylsilylethynyl)pentacene (TIPS-Pen), a widely explored p-type semiconductor, , as the channel material (Figure a). TIPS-Pen molecules exhibit a two-dimensional “brick-wall” packing motif in the solid state, which facilitates efficient charge carrier transport.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we report an optically switchable organic synapse based on a simple OFET structure with 6,13-bis(triisopropylsilylethynyl)pentacene (TIPS-Pen), a widely explored p-type semiconductor, , as the channel material (Figure a). TIPS-Pen molecules exhibit a two-dimensional “brick-wall” packing motif in the solid state, which facilitates efficient charge carrier transport.…”
Section: Introductionmentioning
confidence: 99%
“…From the literature, it has been found that the amorphous polymer poly(triarylamine) (PTAA) can serve as an excellent active layer for OFET-based NO 2 sensors [ 14 , 15 ]. PTAA possesses the highest occupied molecular orbital (HOMO) level of −5.14 eV [ 16 ], enabling stable operation in ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise mechanism of gas detection requires further study, including investigations into gas dynamics (such as diffusion) and device physics. Continued research efforts are aimed at optimizing PTAA-based sensors, which involve the development of novel device structures, surface functionalization techniques, and integration with other materials or technologies to enhance overall sensor performance [ 11 , 14 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%